Lifestyle surveys--the complete answer?. Issue 1 (February 1997) - Dengler, R; Roberts, H; Rushton, L
Abstract : STUDY OBJECTIVES: These were as follows: to study incompleteness of data, herein called item non-response, generated by a self completion questionnaire; to identify the characteristics of item non-responders and the types of questions liable to high item non-response rates; and to discuss possible reasons for item non-response. DESIGN: Item non-response patterns in 12, 307 responders (62%) to a representative postal survey based on a stratified sample drawn from family health services authorities' (FHSA) registers were investigated. MAIN OUTCOME MEASURES: Data were analysed for item non-response in three groups depending on when the questionnaire was returned (wave analysis). The overall completion rate of the questionnaire was examined and the natural logarithm of the proportion of completed questions was used as an outcome variable in multiple regression analysis. Item nonresponse to key questions and questions of different types was examined. RESULTS: Wave analysis: the overall completion rate of the questionnaire was 86% in questionnaires returned before the first reminder and 83%-84% in those sent back after subsequent reminders. Overall pattern of item non-response; respondents failed to complete a mean of 15% and a median of 10% of the questionnaire. All questions in the questionnaire had some item non-response, ranging from 1% to 85%. Completion rates were associated with gender, age, indicators of lower socioeconomic status, and general health status. Individual questions: particular types of questions were liable to have higher item non-response, for example, linked binary questions. CONCLUSIONS: Item non-response in population postal surveys is likely to present problems in the interpretation of data by introducing bias additional to that of total non-response. Item non-response does not increase greatly with later returns, suggesting that the quality of data across responses generated by two reminders is similar. There are obstacles to reducing item non-response, such as respondent error or socioeconomic and health characteristics of the general population, that cannot be totally overcome. However, the evidence that individuals tend to complete only options within questions that apply to them and their positive behaviour is useful information for those designing questionnaires and interpreting survey data.